Use of legume biological nitrogen fixation in crop/livestock production systems - Haque, I. (Wiley, 1992)
Crop livestock production systems in Africa are constrained by wide fluctuations in the quality and quantity of feed resources during the year and by the low availability of nutrients, especially nitrogen and phosphorus, in most soils, which threatens the sustainability of primary production. In mixed farming systems, legumes can be integrated with crops in order to enhance soil fertility, soil structure and crop production and to provide high-quality feed for livestock. Drawing on recent research results from ILCA, this paper discusses phosphorus nutrition and the role of legume biological nitrogen fixation in croping systems on Vertisols and upland soils. It reviews clover screening with regard to phosphorus deficiency in Vertisols and the effect of manure on lucerne grown on an Ultisol. The reorientation of soil science and plant nutrition research at ILCA in the light of these results is briefly outlined.